Exercise, Obesity and CNS Control of Metabolic Homeostasis: A Review - Smith, John K. (Frontiers in Physiology, 2018)
This review details the manner in which the central nervous system regulates metabolic 32 homeostasis in normal weight and obese rodents and humans. It includes a review of the 33 homeostatic contributions of neurons located in the hypothalamus, the midbrain and limbic 34 structures, and the medullary area postrema, nucleus tractus solitarius, and vagus nucleus, and 35 details how these brain regions respond to circulating levels of orexigenic hormones, such as 36 ghrelin, and anorexigenic hormones, such as glucagon-like peptide 1 and leptin. It provides an 37 insight as to how high intensity exercise may improve homeostatic control in overweight and 38 obese subjects. Finally, it provides suggestions as to how further progress can be made in 39 controlling the current pandemic of obesity and diabetes. 40